Estabilidade e habilidade de formação de vidros óxidos - Jiusti, Jeanini (2020)
The glass-forming ability (GFA) is a measure of the easiness of vitrification of a liquid during cooling from the liquidus temperature. The GFA is inversely proportional to the critical cooling rate (Rc), whose determination is laborious. Numerous glass stability parameters (GS = glass stability), based on the characteristic DSC temperatures of glasses, have been suggested in the literature to facilitate the estimation of Rc. 35 GS parameters were analyzed for their ability to estimate the GFA using a rigorous statistical method. The effect of alkaline oxides (R2O) and alkaline earth oxides (RO) on the GFA was also studied. In this work, we proposed and tested a new parameter to estimate the GFA of oxide glasses, which is based on crystallization models and depends on the viscosity, h, and liquidus temperature, Tl (GFA ∝ [h(Tl)/Tl2]). It showed a good correlation with the Rc of various oxide compositions. The study of the GS parameters showed that the KW, KH, and KCR parameters estimate well the GFA of glasses, but all of them depend on Tl. Among the parameters that do not depend on Tl, the KM parameter stood out. The study of the effect of network modifiers pointed out that Li2O results in the worst GFA among the alkalis. In contrast, the alkaline earth elements have a similar effect, regardless of the atomic radius. The order of glass-forming ability for pure network formers is B2O3 > SiO2 > GeO2 > TeO2 > Al2O3. The GS parameters indicated that the compositions with the best GFA are often found in the eutectic points; however, it may be associated with particularities of the structure of the vitreous system.